Six new species and three new records of infaunal alpheid shrimps from the genera Leptalpheus Williams, 1965 and Fenneralpheus Felder & Manning, 1986 (Crustacea, Decapoda) - Anker, Arthur (Zootaxa, 2011)
Several species of the infaunal alpheid genera Leptalpheus Williams, 1965 and Fenneralpheus Felder & Manning, 1986 are described as new or reported from new localities in the tropical western Atlantic and eastern Pacific. In the genus Leptalpheus, five species are described as new: L. marginalis sp. nov. from the Caribbean coast of Colombia; L. penicillatus sp. nov. from the Pacific coast of Panama and Costa Rica; L. azuero sp. nov., L. hendrickxi sp. nov., and L. bicristatus sp. nov., all three from the Pacific coast of Panama. In addition, L. cf. forceps Williams, 1965 and L. felderi Anker, Vera Caripe & Lira, 2006 are reported for the first time from the Caribbean coast of Panama. Several unidentified species of Leptalpheus presently known from incomplete or immature specimens are also reported. In the genus Fenneralpheus, F. orabovis sp. nov. is described as new, whereas F. chacei Felder & Manning, 1986 is reported from the Caribbean coast of Panama, representing the first finding of this species outside its type locality in Florida. The generic diagnoses of both Leptalpheus and Fenneralpheus are emended to accommodate the new species.